Evidence to Impact Pathways: Strengthening Policy Coherence for Sustainable Development - Jonatan Lassa (The Journal of Indonesia Sustainable Development Planning, 2025)
This issue features 15 articles, including a commentary and a book review. The research papers are organized into eight thematic clusters, covering topics such as decentralisation, fiscal transfers, and governance; sustainability assessments in agri-food and health; urban tourism analytics; digital health governance and biopolitics; early childhood education systems and enrollment; land use conversion, mining, and carbon stocks; agri-economics and smallholder production and planning systems; and policy overlaps alongside commentary.